The Atacama Cosmology Telescope: a CMB lensing mass map over 2100 square degrees of sky and its cross-correlation with BOSS-CMASS galaxies. Issue 2 (10th November 2020) - Darwish, Omar; Madhavacheril, Mathew S; Sherwin, Blake D; Aiola, Simone; Battaglia, Nicholas; Beall, James A; Becker, Daniel T; Bond, J Richard; Calabrese, Erminia; Choi, Steve K; Devlin, Mark J; Dunkley, Jo; et al.
ABSTRACT: We construct cosmic microwave background lensing mass maps using data from the 2014 and 2015 seasons of observations with the Atacama Cosmology Telescope (ACT). These maps cover 2100 square degrees of sky and overlap with a wide variety of optical surveys. The maps are signal dominated on large scales and have fidelity such that their correlation with the cosmic infrared background is clearly visible by eye. We also create lensing maps with thermal Sunyaev−Zel'dovich contamination removed using a novel cleaning procedure that only slightly degrades the lensing signal-to-noise ratio. The cross-spectrum between the cleaned lensing map and the BOSS CMASS galaxy sample is detected at 10σ significance, with an amplitude of A = 1.02 ± 0.10 relative to the Planck best-fitting Lambda cold dark matter cosmological model with fiducial linear galaxy bias. Our measurement lays the foundation for lensing cross-correlation science with current ACT data and beyond.